Workshop Pembuatan Terarium sebagai Media Pembelajaran Bagi Guru Biologi di SMA Islam Al Azhar NW Kayangan - Safnowandi, Safnowandi; Dharmawibawa, Iwan Doddy; Efendi, Ismail; Harisanti, Baiq Muli; Abidin, Zainal (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2025)
Terrarium making workshop as a learning media for Biology teachers at SMA Islam Al Azhar NW Kayangan, Batu Layar District, West Lombok Regency aims to introduce and train Biology teachers in utilizing Terrarium as an effective learning aid. Terrarium as a miniature ecosystem that can imitate natural conditions, is believed to be able to improve students' understanding of Biology concepts, especially those related to ecosystems, water cycles, and interactions between organisms. This activity can provide practical skills to teachers in designing and making Terrariums that can be used in classroom learning, as well as encourage the application of more creative and interesting learning methods. Through this workshop, teachers can implement Terrarium-based learning media to improve students' motivation and understanding of Biology materials at SMA Islam Al Azhar NW Kayangan, Batu Layar District, West Lombok Regency. The results of this community service activity show that the teachers are very enthusiastic and feel the benefits of this activity in the learning process. Biology teachers and their students looked very enthusiastic in paying attention to the presentation of materials and demonstrations of making Terrariums. Making Terrariums is very rarely done by Biology teachers in their schools. With this activity, teachers are excited to be creative and innovative in making various learning media, especially in Biology subjects. This activity is expected to be improved again by continuing to pay attention to the needs of teachers with other materials, so that it can open the insights of Biology teachers in innovating to create various learning media that are needed.